HUBUNGAN KEPEMIMPINAN TRANSFORMASIONAL DAN KOMUNIKASI TERHADAP KINERJA PT BANK MANDIRI CABANG MAMPANG PRAPATAN - Liberto Jonathan; Nenny Anggraini; Desideria Regina (Universitas Kristen Indonesia, 2023)
In maintaining work stability in running a company. So, leaders in a company must know what their functions and duties are in running the company so that the company they lead can develop, the role of leaders can affect moral, job satisfaction, qualities, and especially level of achievements of an organizational. Because a phenomenon of decreasing employee performance in several companies and frequent turnover in the company, therefore the company's success in achieving the goals to be achieved depends on the leader, effectively and efficiently in carry out management process. Therefore, communication can be main instrument of competitive advantage, i.e., if communication helps in the smooth running of the organization's strategy. If employees have good communication at work, he no longer treats the place work as a place to earn money. The employee will treat his workplace like a home or family that he also owns and he feels partly responsible for bringing the company to developments. These researched was carry out with a quantitative approached, namely an approached use data analyst of numeric or numbers, by mean of a survey, namely researches that take a numbering of sample populations by distributing questionnaires as main data. which is entered to obtain objective data variable factors, namely transformational leadership style and communication that affect performance, to strengthen the truth of the data obtained from the field. Transformational Leadership Variable (X1) has a significant positive relationship or correlation to employee performance (Y) of 0.883. This is found at the Transformational leadership significant level of 0.001 which is small than 0.05 or 0.001 0.05. The most significant relationship of Transformational Leadership to employee performance is, inspiration and charisma as well as creating a good cooperative atmosphere for employees. We recommend that the management of PT. Bank Mandiri Mampang Prapatan branch continues to pay attention to the character of the leaders chosen in running the company's wheels and maintain leaders who are able to inspire and have charisma in leading and are able to create a good performance atmosphere for employees to improve employee performance as well as communication so that communication can be continued and improved. has been running at this time so that the improvement of employee performance will continue to increase. Keywords: Transformational leadership, communication, Performance